Cara Anak Deafblind Berkomunikasi: Penggunaan Bahasa Isyarat Taktil (Jurnal Insan Pendidikan dan Sosial Humaniora, 2024)
Children with visual and hearing impairments experience barriers to communication, and tactile cueing systems present a more effective communication solution for people with multiple sensory disabilities. Researchers used the literature study research method and found references related to the title which were then reviewed as a whole. Tactile sign systems combine sign language and hand touch. As a communication method, tactile sign systems have their own advantages and challenges.